Tumor extravasation and infiltration as barriers of nanomedicine for high efficacy: The current status and transcytosis strategy. (May 2020) - Zhou, Quan; Dong, Chengyuan; Fan, Wufa; Jiang, Haiping; Xiang, Jiajia; Qiu, Nasha; Piao, Ying; Xie, Tao; Luo, Yingwu; Li, Zichen; Liu, Fusheng; Shen, Youqing
Abstract: Nanotechnology-based drug delivery platforms have been explored for cancer treatments and resulted in several nanomedicines in clinical uses and many in clinical trials. However, current nanomedicines have not met the expected clinical therapeutic efficacy. Thus, improving therapeutic efficacy is the foremost pressing task of nanomedicine research. An effective nanomedicine must overcome biological barriers to go through at least five steps to deliver an effective drug into the cytosol of all the cancer cells in a tumor. Of these barriers, nanomedicine extravasation into and infiltration throughout the tumor are the two main unsolved blockages. Up to now, almost all the nanomedicines are designed to rely on the high permeability of tumor blood vessels to extravasate into tumor interstitium, i.e., the enhanced permeability and retention (EPR) effect or so-called "passive tumor accumulation"; however, the EPR features are not so characteristic in human tumors as in the animal tumor models. Following extravasation, the large size nanomedicines are almost motionless in the densely packed tumor microenvironment, making them restricted in the periphery of tumor blood vessels rather than infiltrating in the tumors and thus inaccessible to the distal but highly malignant cells. Recently, we demonstrated using nanocarriers to induce transcytosis of endothelial and cancer cells to enable nanomedicines to actively extravasate into and infiltrate in solid tumors, which led to radically increased anticancer activity. In this perspective, we make a brief discussion about how active transcytosis can be employed to overcome the difficulties, as mentioned above, and solve the inherent extravasation and infiltration dilemmas of nanomedicines.